Low-complexity optimal MPSK detection for spatial modulation - Hong-zhi MEN; Ming-lu JIN (Tongxin xuebao)
The low-complexity optimal SM detection algorithm for MQAM signal detection had been proposed,but no similar method was found for MPSK signal.The problem of low-complexity detection for MPSK signal was considered in SM systems.Utilizing 2-D vector quantization of ML demodulation and the property of MPSK constellation,a low-complexity optimal detection which is independent to modulation order was developed.Since the approach avoids the exhaustive searching on signal constellation space,the computational complexity can be significantly reduced.The proposed detection algorithm can provide the identical performance with ML-optimum detector and has lower computational complexity.Therefore,it has both theoretical and practical significance.The proposed algorithm is of great significance in the large antenna and green communication technology.